Role of RAGE and Its Ligands on Inflammatory Responses to Brain Tumors - Otazu, Griffith Kyle; Dayyani, Mojtaba; Badie, Behnam (Frontiers in Cellular Neuroscience, 2021)
Gliomas, the most common form of brain cancer, can range from relatively slow-growing low-grade to highly aggressive glioblastoma that has a median overall survival of only 15 months despite multimodal standard therapy. Although immunotherapy with checkpoint inhibitors has significantly improved patient survival for some cancers, to date, these agents have not shown consistent efficacy against malignant gliomas. Therefore, there is a pressing need to better understand the impact of host inflammatory responses on the efficacy of emerging immunotherapy approaches for these resistant tumors. RAGE is a multi-ligand pattern recognition receptor that is activated in various inflammatory states such as diabetes, Alzheimer’s disease, cystic fibrosis, and cancer. Low levels of RAGE can be found under normal physiological conditions in neurons, immune cells, activated endothelial, and vascular smooth muscle cells, but it is over-expressed under chronic inflammation due to the accumulation of its ligands. RAGE binds to a range of damage-associated molecular pattern molecules (DAMPs) including AGEs, HMGB1, S100s, and DNA which mediate downstream cellular responses that promote tumor growth, angiogenesis, and invasion. Both In vitro and in vivo studies have shown that inhibition of RAGE signaling can disrupt inflammation and cancer progression and metastasis. Here, we will review our current understanding of the role of RAGE pathway on glioma progression and how it could be exploited to improve the efficacy of immunotherapy approaches.